Hepatic Steatosis among Obese Children and Adolescents (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Chronic liver disease, known as non- alcoholic fatty liver disease (NAFLD) is a metabolic complication of obesity. Hepatic steatosis is an entity in the spectrum of NAFLD, ranges from simple steatosis to advanced fibrosis and cirrhosis.Objective: To identify prevalence of hepatic steatosis and to assess correlation between hepatic steatosis and anthropometry, SGPT and metabolic abnormalities of obese children and adolescents.Methodology: This cross sectional study included 50 obese children and adolescents, attending the Endocrine OPD of Dept. of Paediatrics in BIRDEM from June 2009 to December 2009. BMI e 95th centile for age and sex was used as an anthropometric marker to diagnose obesity. Obesity with any dismorphism, endocrine or chromosomal abnormalities were excluded. Fasting blood samples were collected for measurement of SGPT, blood glucose, lipid profile, FT4 &TSH. Sonographic findings of fatty liver include increased echogenicity of liver, blurring of vascular margins and increased acoustic attenuation.Results: Mean age of the children was 11.24 (8-18) years. High SGPT level was prevalent among 36% of obese children. The most prevalent abnormal lipid profile was high TG (78%) followed by high cholesterol level (68%). The prevalence of hepatic steatosis was 36% with male predominance (M 72.2%, F 27.8%). Mild hepatic steatosis was 72% followed by moderate 28%. High SGPT, high cholesterol and LDL were more prevalent in children with hepatic steatosis in comparison to children without steatosis (P